Design, synthesis and evaluation of novel thieno[2,3d]pyrimidine derivatives as potent and specific RIPK2 inhibitors - Misehe, Mbilo; Šála, Michal; Matoušová, Marika; Hercík, Kamil; Kocek, Hugo; Chalupská, Dominika; Chaloupecká, Ema; Hájek, Miroslav; Boura, Evzen; Mertlíková-Kaiserová, Helena; Nencka, Radim (Bioorganic & medicinal chemistry letters, 2024)
In human cells, receptor-interacting protein kinase 2 (RIPK2) is mainly known to mediate downstream enzymatic cascades from the nucleotide-binding oligomerization domain-containing receptors 1 and 2 (NOD1/2), which are regulators of pro-inflammatory signaling. Thus, the targeted inhibition of RIPK2 has been proposed as a pharmacological strategy for the treatment of a variety of pathologies, in particular inflammatory and autoimmune diseases. In this work, we designed and developed novel thieno[2,3d]pyrimidine derivatives, in order to explore their activity and selectivity as RIPK2 inhibitors. Primary in vitro evaluations of the new molecules against purified RIPKs (RIPK1-4) demonstrated outstanding inhibitory potency and selectivity for the enzyme RIPK2. Moreover, investigations for efficacy against the RIPK2-NOD1/2 signaling pathways, conducted in living cells, showed their potency could be tuned towards a low nanomolar range. This could be achieved by solely varying the substitutions at position 6 of the thieno[2,3d]pyrimidine scaffold. A subset of lead inhibitors were ultimately evaluated for selectivity against 58 human kinases other than RIPKs, displaying great specificities. We therefore obtained new inhibitors that might serve as starting point for the preparation of targeted tools, which could be useful to gain a better understanding of biological roles and clinical potential of RIPK2.
Keywords: NOD; Receptor-interacting protein kinase 2; signální transdukce; Signal Transduction; Thieno[2,3d]pyrimidine derivative; RIPK2; Kinase inhibitor; Inflammation; Humans; Receptor-Interacting Protein Serine-Threonine Kinase 2; protein-serin-threoninkinasa 2 interagující s receptory; lidé; zánět